Peanut-shaped ZnO nanostructures: A driving force for enriched antibacterial activity and their statistical analysis. Issue 1 (January 2020) - Wahab, Rizwan; Khan, Farheen; Al-Khedhairy, Abdulaziz A.
Abstract: The nanostructures made of ZnO have a special place in nanotechnology because of the broader applications in various optoelectronic devices. The new shapes and sizes have different synergic effects on biological entities. Because of the broader applications, the current work was aimed at the synthesis, characterisation, antibacterial testing, and statistical validation of peanut-shaped ZnO nanostructures (ZnO-PNTs). They were prepared via a chemical process with precursor zinc nitrate and sodium hydroxide at ∼80 °C for 3 h with refluxing. The bacteriostatic properties of prepared nanostructures were tested on different bacterial species, namely, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, and Klebsiella pneumoniae at various concentrations (5–45 μg/mL) of ZnO-PNTs, assessed via UV–visible spectrophotometry. The results and their assessment revealed that a minute concentration of ZnO-PNTs in the form of a solution reduces the population of bacteria effectively, and the effective concentration was found to be 5 μg/mL for all the tested pathogens. Additionally, the chemical and biological mechanism of action was explored for ZnO-PNTs toward the bacterial species under study. The ZnO-PNTs were well characterised by X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, and fourier transform infrared spectroscopy, which indicated that well-grown nanostructures at a very low concentration effectively inhibit the growth of bacteria (reduce their concentration), as confirmed by UV–visible spectrophotometry. On the basis of obtained results and their analysis, it is expected that ZnO-PNTs will be applied as a biofilm against various food pathogens in near future. Statistical evaluation was also conducted for the bacterial suspensions with the nano structures.